2023
DOI: 10.1002/pa.2863
|View full text |Cite
|
Sign up to set email alerts
|

Public administration in smart city: A bibliometric analysis

Abstract: The role of the public administration is crucial for the development of smart cities. Several scholars have highlighted the need for greater contributions focused on the relationship between public administration and smart cities. This work aims to map the contributions on the topic highlighting the status of the field in the recent years. A bibliometric analysis was performed on a sample of articles published in business and management journals. The analysis was carried out using the R‐studio Bibliometrics pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This (social responsibility) can be inculcated through the use of appropriate education programmes, and the provision of relevant advice and guidance concerning the processes and benefits of a smart city. This has been shown by other studies to be an effective approach to building public participation in the context of smart cities [46,101,102].…”
Section: Discussionmentioning
confidence: 54%
“…This (social responsibility) can be inculcated through the use of appropriate education programmes, and the provision of relevant advice and guidance concerning the processes and benefits of a smart city. This has been shown by other studies to be an effective approach to building public participation in the context of smart cities [46,101,102].…”
Section: Discussionmentioning
confidence: 54%
“…The impact of urban innovation policies is usually analyzed from a top-down perspective. Noticeably, some studies have been recently carried out to quantify the impact of public administration measures on urban development [64]. On the one hand, in China, an extensive study evaluates the agglomeration model and allocation of urban resources under the urban administrative hierarchy in 281 cities showing the important impact of including environmental aspects on urbanization [65].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Facilitating these changes is not straightforward, and can require significant support and encouragement from management. Lack of appropriate support could result in the failure of the overall DT process [10,14]. Previous research has shown that employees often resist change due to a number of factors, such as familiarity with current practices, known as inertia [15], or due to a perceived threat to their job [4,16].…”
Section: Introductionmentioning
confidence: 99%